Contagem via funções geradoras - Brasiliano, Marina Miranda Alves [UNIFESP] (2020)
Motivated by a question from the National High School Examination - Enem - 2017, the present work, aiming at improving teacher’s mathematics knowledge about Enumerative Combinatorics, presents as generating functions an important tool to solve problems, mainly the ones in which repetitions in the choice of objects are allowed. For this purpose, this dissertation presents an intuitive vision of generating function, as well as in the context of weighted sets and series of formal powers. Finally, a didactic proposal is presented so that such a counting tool can be used by the teacher and his students.